Birds of Bosque Protector Jerusalem, Guayllabamba Valley, Ecuador - Cadena-Ortis, Héctor (2015)
The Ecuadorian inter-Andean dry valleys are highly affected by human intervention. Currently, less than 5% of the original vegetation cover of these valleys remains on creeks and hillsides. Bosque Protector Jerusalem (1,110 ha), in the upper Guayllabamba River valley, protects the largest remnants of inter-Andean dry forest in Ecuador. Here, we present data derived from two recent studies (from 2009 to 2013), as well as information collected by other authors in previous studies, between the years 2002 and 2009. We present a unified list of 75 species of birds, accounts for species of particular interest, new distributional records, and considerations about the conservation of the study area. © 2015 Check List and Authors.